2020
DOI: 10.1109/access.2020.2992773
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Two-Server Ranked Dynamic Searchable Encryption Scheme

Abstract: Searchable encryption (SE) allows users to search over encrypted data without decrypting. In most existing SE schemes, server returns all matched files without relevance ranking, and the update mechanism are suffering with high communication and computation cost, which are not efficient enough to satisfy the real-life dynamic scenario. Addressing the above issues, we proposed TS-RDSE-a Two-Server Ranked Dynamic Searchable Encryption scheme. We integrate orthogonal vector and efficient homomorphic encryption cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, despite this, a considerable percentage of SE schemes utilize FHE due to its potential benefits (38% use FHE for 57% of systems using PHE). Finally, we also observed that more than a half of the schemes that rely on a PHE scheme use either the Paillier cryptosystem [52,59,64,65,69], a combination of the Paillier cryptosystem with GM [63,71], or the Paillier cryptosystem with threshold decryption [67]. The reason that so many approaches choose to use the Paillier cryptosystem (or any other variations) is the simplicity and security of the scheme, as well as the number of existing implementations freely available.…”
Section: Types Of He Schemes Used In Sementioning
confidence: 95%
See 4 more Smart Citations
“…However, despite this, a considerable percentage of SE schemes utilize FHE due to its potential benefits (38% use FHE for 57% of systems using PHE). Finally, we also observed that more than a half of the schemes that rely on a PHE scheme use either the Paillier cryptosystem [52,59,64,65,69], a combination of the Paillier cryptosystem with GM [63,71], or the Paillier cryptosystem with threshold decryption [67]. The reason that so many approaches choose to use the Paillier cryptosystem (or any other variations) is the simplicity and security of the scheme, as well as the number of existing implementations freely available.…”
Section: Types Of He Schemes Used In Sementioning
confidence: 95%
“…In the same year, Li et al [64], proposed a two-server ranked dynamic SE scheme (TS-RDSE), meant for a single-user setting, which supports multi-keyword search. This scheme uses two cloud servers to perform the searching and sorting, with one of them being responsible for storing the encrypted data and the other one for storing the secret key.…”
Section: Ranked Searchmentioning
confidence: 99%
See 3 more Smart Citations